2023
DOI: 10.1002/fft2.246
|View full text |Cite
|
Sign up to set email alerts
|

New insights into chemical compositions and health‐promoting effects of black beans (Phaseolus vulgaris L.)

Abstract: Black beans (Phaseolus vulgaris L.) are most widely consumed in China, India, and America due to their unique taste and potent health benefits attributed to their higher content of phytochemicals. Researchers have extensively explored the phenolic profile and biological properties of black beans. This paper first attempt to review nutritional composition, phytochemical profile, and health‐promoting properties of black beans. Black beans are reported to exhibit potent antioxidant, antidiabetic, anticancer, anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 108 publications
0
7
0
Order By: Relevance
“…In contrast, Fonseca et al [ 10 ] reported quercetin-3-D-galactoside, cyanidin-3-glucoside, gallic acid, caffeic acid, daidzin, sinapic acid, naringenin, rosmarinic acid, catechin, myricetin, and ferulic acid in raw and purified native black bean extracts. Native black bean phytochemical profile varies according to the cultivar, seed selection, and farming conditions where they were cultivated [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Fonseca et al [ 10 ] reported quercetin-3-D-galactoside, cyanidin-3-glucoside, gallic acid, caffeic acid, daidzin, sinapic acid, naringenin, rosmarinic acid, catechin, myricetin, and ferulic acid in raw and purified native black bean extracts. Native black bean phytochemical profile varies according to the cultivar, seed selection, and farming conditions where they were cultivated [ 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…Commonly found in nature are the glycoside forms. Delphinidin-3- O -glucoside (Dp3G) is prevalent in wine, eggplant, black bean, and various berries, while petunidin-3- O -glucoside (Pt3G) is abundant in black bean, black goji, and purple potatoes. , The anthocyanins demonstrate various health benefits, including antioxidant, anti-inflammatory, anticancer, and antiobesogenic properties; immunomodulatory diseases; and regulating glucolipid metabolic disease . The biological activity of anthocyanins is based on their excellent antioxidant capacity, and studies have shown that the antioxidant efficacy of Dp3G and Pt3G surpasses that of cyanidin-3- O -glucoside (C3G) .…”
Section: Introductionmentioning
confidence: 99%
“…Among legumes, the common bean (Phaseolus vulgaris) is among the planet's most widespread crops and presents remarkable variability in terms of varieties, shapes, and colors [20][21][22][23]. Borlotti beans, cannellini beans, pinto beans, navy beans, red kidney beans, and black beans are just a few examples.…”
Section: Introductionmentioning
confidence: 99%
“…Black beans are kidney-shaped, sweetflavored, and black-colored, with a small white spot. They are the legume of choice for Latin American and African countries, thanks to their high nutritive profile: they are a good source of proteins containing most essential amino acids, especially lysine, and their protein content is comparable to milk, eggs, soybeans, and meat [20]. They are also rich in polyphenols, which are mainly present in the coat of legume seeds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation